Multiperspectivity as a Process of Understanding and Reflection: Introduction to a Model for Perspective-Taking in Geography Education - Dina Vasiljuk; Alexandra Budke (MDPI AG, 2021)
Perspective-taking is an essential competency because it enables a better understanding of complex issues or conflicts with various actors and different points of view involved. However, no competency model for perspective-taking has been provided in geography education to date, which is why a respective model was developed in this study. The model was then applied by analysing 28 articles from four practice journals of geography education from German-speaking countries. This analysis focused on the dimensions of the perspective-taking competencies that were required by respective tasks within the lesson concepts. The results show that the tasks hardly promoted competence-oriented geography teaching in terms of perspective-taking. Therefore, the competency model could be a suitable tool for analysing and developing teaching materials that implement perspective-taking.